Academic Achievement for Fifth-Grade Students in Elementary and Intermediate School Settings: Grade Span Configurations - Julie P. Combs; David Clark; George W. Moore; Anthony J. Onwuegbuzie; Stacey L. Edmonson; John R. Slate (Arizona State University, 2011)
Few researchers have addressed student achievement outcomes as a function of grade configurations for older elementary-aged students. Thus, this study was designed to determine differences between studentsâ Grade 5 reading and mathematics achievement in elementary schools (Kâ5) as compared to intermediate schools (Grade 5, 5â6) for 5 academic years. Using archival statewide data, researchers used a rigorous five-step distance-based formula to match elementary schools to intermediate schools on four demographic/school characteristic variables. Students in K-5 settings attained statistically significantly higher levels of reading and mathematics achievement than did their counterparts, with moderate mean effect sizes of 0.37 and 0.47.